Influence of functional insufficiency of the thyroid gland on the bone and cartilage tissue. - Nosivets, D. S. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. Diseases of the thyroid gland are an urgent problem of modern society in connection with the wide, constant spread of this pathology and with somatic, reproductive and mental disorders associated with these diseases. The negative effect of thyroid hormone dysfunction on the functional state of organs and systems is due to the key role of thyroid hormones in metabolic processes. It is known that metabolic disorders negatively affect the state of bone and cartilage tissue, cause the development of a number of pathological conditions among which osteoarthrosis is certainly important. Objective - to study the structural histological changes of the bone and cartilage tissue on the background of the hypofunction of the thyroid gland in experimental animals. Methods. The work used 60 white mature outbred rats of both sexes weighing 180-230 g. Experimental modeling of hypothyroidism was the use of a 0.02% solution of carbimazole (5 mg per 250 ml of saline) in the rats' drinking diet for 6 weeks. Comparative characteristics were carried out on the basis of studying the histological structure of the articular cartilage of the knee joints of intact rats. Results. The histological assessment of the state of bone and cartilage tissue in an experimental model of hypothyroidism has shown that the structure of cartilage and subchondral bone undergoes certain changes. The synovial membrane is sharply enlarged in thickness, its structure is friable, non-uniform, in some places destruction sites are observed. The surface of the perchondrium has an uneven edge, sometimes vacuolized. Conclusion. Hypofunction of the thyroid gland shows signs of inflammation of the synovial membrane, a violation of the structure of the perichondrium with signs of swelling, a violation of the trophism of the deep layers of cartilage, accompanied by destruction of a number of chondrocytes, as well as changes in the histochemical properties of amorphous substance.